2020
DOI: 10.1093/braincomms/fcaa138
|View full text |Cite
|
Sign up to set email alerts
|

5′ValCAC tRNA fragment generated as part of a protective angiogenin response provides prognostic value in amyotrophic lateral sclerosis

Abstract: Loss-of-function mutations in the ribonuclease angiogenin are associated with amyotrophic lateral sclerosis. Angiogenin has been shown to cleave transfer RNAs during stress to produce ‘transfer-derived stress-induced RNAs’ (‘tiRNAs’). Stress-induced tRNA cleavage is preserved from single-celled organisms to humans indicating it represents part of a highly conserved stress response. However, to date the role of tRNA cleavage in amyotrophic lateral sclerosis remains to be fully elucidated. To this end, we perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…The function of tRNA fragments is still relatively unknown but they can be actively cleaved by angiogenin, have been shown to affect RNA translation and be induced by stress [ 30 , 31 ]. In fact, tRNA fragments have been proposed previously as biomarkers for ALS, including in our own studies [ 18 , 32 ]. Most interestingly though, one study, found that 5′ fragments derived from tRNA-ValCAC had elevated release from neural cells and cleavage in mouse models, and consequently had prognostic value when tested in human samples [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…The function of tRNA fragments is still relatively unknown but they can be actively cleaved by angiogenin, have been shown to affect RNA translation and be induced by stress [ 30 , 31 ]. In fact, tRNA fragments have been proposed previously as biomarkers for ALS, including in our own studies [ 18 , 32 ]. Most interestingly though, one study, found that 5′ fragments derived from tRNA-ValCAC had elevated release from neural cells and cleavage in mouse models, and consequently had prognostic value when tested in human samples [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Recent work has identified 5'tiRNA Val−CAC as a potential biomarker for ALS. This tiRNA was found to be increased in the spinal cord of SOD1 G93A mice and is significantly increased in the serum of patients with slow progressing ALS [120].…”
Section: Ncrna Biomarkers In Amyolateral Sclerosismentioning
confidence: 92%
“…Interestingly, the Ang-generated tiRNA 5′ValCAC is increased in SOD1 G93A mice at symptom onset and correlate with Ang expression and slower disease progression. Furthermore, increased 5′ValCAC in ALS patient serum samples is correlated with slower disease progression [120].…”
Section: Amyolateral Sclerosismentioning
confidence: 99%
“…Initially, tiRs were found to be upregulated under various stress conditions, giving them the name stress-induced tRNA halves. The RNase IV enzyme, angiogenin (ANG), was identified to be the enzyme responsible for tiR production under stress conditions and the 5′-terminal oligoguanylate (TOG) motif was found to be present in these tiRs ( Ivanov et al, 2011 ; Saikia et al, 2014 ; Honda et al, 2015 ; Liu S. et al, 2018 ; Hogg et al, 2020 ). However, ANG KO does not reduce the levels of basally expressed (non-stress induced) tiRs ( Su et al, 2019 ).…”
Section: Biogenesis Of Trna Fragments and Trna Halvesmentioning
confidence: 99%